Confirmation bias and herding behavior across the housing markets - Taewoo You (Humanities & Social Sciences Communications)
Abstract This article investigates the global herding behavior across the housing markets. Using the OECD quarterly data from 1970 to 2022, I find that global herding is contingent on the concurrent interplay between the US price-to-rent regimes and average price changes. Evidence is consistent with the proposed view that global herding is displayed when investors use the pseudo signal flying from the US market for confirmation. I also find that valuation anchors, such as price-to rent and price-to-income, also display correlated behaviors among countries, suggesting the existence of spurious herding as a result of investors’ common responses to changes in fundamental factors. Even after the effects of the fundamental anchors are purged away, evidence on global herding is substantial, suggesting that the global herding behavior is psychological. This article asserts that the global herding behavior is driven by investors’ confirmation bias boosted by coincidence between average price changes and the expectation on the US housing market. The evidence is consistent with the view that investors are overconfident on the noisy public information and the unproven belief concerning the association between the external public signal and ex post house price changes.